Manufacture of sintered aggregate using washing aggregate sludge and ground granulated blast furnace slag: Characterization of the aggregate and effects on concrete properties - Ozkan, Hakan; Kabay, Nihat (ELSEVIER SCI LTD, 2022)
The aggregate occupies the highest volume of concrete and alternative methods to replace it using waste materials or by-products are required which can consequently preserve the natural resources. This paper investigates the utilization of washing aggregate sludge (WAS) waste generated from a local aggregate quarry and ground granulated blast furnace slag (GGBFS) to manufacture sintered aggregate. The properties of sintered aggregate were characterized by physical and mechanical tests and microstructural analysis. The aggregate was incorporated in concrete as a substitute for the coarse aggregate to determine its effects on the physical, mechanical, and durability properties. Test results showed that the inclusion of sintered aggregate slightly reduced the oven-dry density and considerably increased the water absorption and permeable voids of concrete. The compressive strength and modulus of elasticity of concrete decreased by up to 16 and 15%, respectively, with increased sintered aggregate ratio. The chloride ion penetrability and chloride migration coefficient of the concrete insignificantly changed with the incorporation of sintered aggregate. The research outcomes indicated the possibility of manufacturing sintered aggregate using WAS and GGBFS and its efficient utilization in concrete production and the optimum replacement ratio of sintered aggregate was found as 30% which yielded 28-day compressive strength of more than 50 MPa and comparable durability properties with reference concrete.
Keywords: Washing aggregate sludge; Ground granulated blast furnace slag; Sintered aggregate; Concrete; Physical properties; Mechanical properties; Durability; FLY-ASH; LIGHTWEIGHT AGGREGATE; SEWAGE-SLUDGE; PELLETIZATION PROCESS; MICROSTRUCTURE; MINERALOGY; BINDERS; Construction & Building Technology; Engineering; Materials Science